Exploring Community Resistance to Coronavirus (COVID-19) Pandemic Preventive Information Protocols in Mando Area of Kaduna State, Nigeria - Lawal Umar, Abdulkareem Abubakar (IJoLIS, 2024)
Purpose: This study explored commnity resistance to coronavirus pandemic preventive information protocols in Mando area of Kaduna State, Nigeria.